2022
DOI: 10.1155/2022/3911326
|View full text |Cite|
|
Sign up to set email alerts
|

Feasibility Study on the Integration of Innovation and Entrepreneurship Education and Occupational Therapy Training Mode for College Students Based on Big Data

Abstract: With the development of information technology, the status of the traditional teaching method combining chalk and blackboard is declining. People need a novel teaching method to reform traditional education, so the hybrid teaching mode combining the advantages of both is produced and has become a major research hotspot in the field of education technology at present. Further accelerating the reform of innovation and entrepreneurship teaching in higher education institutions and improving students’ innovation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…to 90.2 compared with two different teaching methods. Similarly, Zhang et al 13 14 investigated the in uence and effect on "SPOC + ipped classroom" on physical education students' learning motivation and found that it had a positive impact of the video lectures on student's motivation on basketball skills and promoted their motivation autonomy. The conception of SPOC claimed for independent study.…”
Section: Discussionmentioning
confidence: 99%
“…to 90.2 compared with two different teaching methods. Similarly, Zhang et al 13 14 investigated the in uence and effect on "SPOC + ipped classroom" on physical education students' learning motivation and found that it had a positive impact of the video lectures on student's motivation on basketball skills and promoted their motivation autonomy. The conception of SPOC claimed for independent study.…”
Section: Discussionmentioning
confidence: 99%
“…Warner et al studied how to cultivate students' innovation and entrepreneurship ability under innovative education by giving play to their subjective initiative in cognition and practice and paying attention to the development of students' creative consciousness, spirit, and ability [17]. Yang et al selected two indicators of innovation spirit and entrepreneurial ability as the research objectives to investigate the impact of mass entrepreneurship education on students' innovation and entrepreneurial ability [18]. Ding et al used the neural network method to evaluate college students' innovation and entrepreneurship ability.…”
Section: Selection Of Research Variablesmentioning
confidence: 99%
“…With the rapid development of network technology, an increasing number of countries began to try informatization and integration of educational resources 1 . Hence, the occurrence of massive open online courses (MOOCs) in 2012 has reformed traditional teaching boundaries in the past few years 2 .…”
Section: Introductionmentioning
confidence: 99%